2021
DOI: 10.1111/pbr.12946
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐genome resequencing and transcriptome analysis provide insights on aphid‐resistant quantitative trait loci/genes in Sorghum bicolor

Abstract: The sorghum aphid (Melanaphis sacchari) has emerged as a serious pest for Sorghum bicolor and a major factor limiting its production worldwide. In this study, whole‐genome resequencing of resistant and susceptible bulks from a recombinant inbred line (RIL) population was conducted together with transcriptome analysis of the parent to identify genes underlying aphid resistance. In the NGS‐based bulked segregation analysis (BSA), using a total of 920,389 genome‐wide high‐confidence markers, four QTLs, qtlMs‐6.1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 46 publications
2
17
0
Order By: Relevance
“…Some studies have attempted to understand the molecular basis of this interaction in sorghum as monogenic, though it is believed to be oligogenic and polygenic [23][24][25]56 . Most of the studies highlighted the importance of RMES1 locus located on SBI-06 and the causative variants around this region to be the major resistance gene for sugarcane aphid resistance in sorghum depending on the source of resistance used in these studies 24,25,27,56 . SCA resistance is monogenic (single locus) for RME6 ACK60 x RTx2783.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Some studies have attempted to understand the molecular basis of this interaction in sorghum as monogenic, though it is believed to be oligogenic and polygenic [23][24][25]56 . Most of the studies highlighted the importance of RMES1 locus located on SBI-06 and the causative variants around this region to be the major resistance gene for sugarcane aphid resistance in sorghum depending on the source of resistance used in these studies 24,25,27,56 . SCA resistance is monogenic (single locus) for RME6 ACK60 x RTx2783.…”
Section: Discussionmentioning
confidence: 99%
“…Among aphid resistance traits, the maximum number of markers,16, was identi ed on SBI-06. Recent studies have speci cally dissected regions around the RMES1 locus and found several NBS-LRR containing genes that were associated with resistance gene products 25,27,56 . In our investigation, we were able to locate LRR motifs and Avr9 elicitor response protein within 200 kb region for markers associated with aphid damage and aphid count on SBI-06.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations